The Impact of Intervention on Sexual Practices of HIV Positive Individuals in Southeast Nigeria - S. N. Obi; N. A. Ifebunandu; H. E. Onah; A. K. Onyebuchi (Hindawi Limited, 2009)
Objective. To describe the impact of repeating behavioral educational intervention on sexual practices of HIV positive individuals. Method. A prospective cohort study of HIV positive individual was conducted in southeast Nigeria from June 2007 to May 2008. Information on sexual practices was collected at initial visit; education was given and its impact was evaluated afterwards. Results. Knowledge about risk of unprotected intercourse increased by 41%, condom use by 27% (𝑃<.001) and consistent condom use by 55% (𝑃<.001). The significant predictors of consistent condom use include male gender, multiple sexual partner, as well as good knowledge of HIV transmission, higher educational status and being married. Non use of condom at postintervention survey were characterized by female gender (𝑛=4), monogamous relationship (𝑛=10), little or no education (𝑛=10), and unmarried (𝑛=7) respondents. Conclusion. Repeated behavioral education intervention improves consistent condom use among HIV positive individuals and will help curb the spread of HIV/AIDS.